SOCIAL SCIENCE SCHOLARS PERCEPTION TOWARDS OPEN ACCESS AND INSTITUTIONAL REPOSITORIES - Gunasekera, Chamani (PEOPLE: International Journal of Social Sciences, 2017)
The main objective of this study is to explore the attitudes and knowledge about open access publishing and institutional repositories of social science scholars and their participation towards university digital repository. Questionnaire based survey method was employed and the self-administered questionnaires were distributed among all permanent academic staff members in the Faculty of Arts, University of Peradeniya, Sri Lanka on May, 2016 and out of 192, 99 duly completed questionnaires were received making a 51.6% response rate. The results revealed that only 48% of the respondents had knowledge about open access publishing and nearly 22 % of them never heard about the term “open access”. These results gave an insight that the majority of the respondents are not familiar with the term of open access. The results further revealed that most of the respondents learnt about the institutional repositories as a result of a web search engine, information provided at the faculty or meetings held in the university and by working in subject based archives. Only 51% of the respondents were aware of the university digital repository and 36% mentioned that they were not aware of it. Of the respondents, 40% mentioned the university digital repository is either very important or important and 38% agreed that the establishment of institutional repository for the University of Peradeniya will enhance the global reputation of the university. The interesting finding is that 57% of the respondents reported their willingness to contribute to the university digital repository in future while 14% of them were not willing to contribute in future.